Mitochondrial Fatty Acid Oxidation and Susceptibility to Endotoxin in Acute Liver Injury - Farrar, W. Edmund (1965)
Farrar, W. Edmund, Jr. (Walter Reed Army Institute of Research, Washington, D.C.), Laurence M. Corwin, and Thomas H. Kent. Mitochondrial fatty acid oxidation and susceptibility to endotoxin in acute liver injury. J. Bacteriol. 90:1365–1372. 1965.—Acute liver injury was produced in guinea pigs with three chemically unrelated hepatotoxins: CCl(4), allyl alcohol, and dl-ethionine. The effects of these agents on liver morphology, susceptibility of animals to Escherichia coli endotoxin, endotoxin-inactivating ability of tissue homogenates, and substrate oxidation by liver mitochondria were studied. CCl(4) markedly reduced oxidation of all substrates studied except succinate, impaired the ability of liver homogenates to detoxify endotoxin in vitro, and increased the susceptibility of animals to the lethal effect of endotoxin by 150-fold. Allyl alcohol produced a severe morphological lesion in the liver but did not impair fatty acid oxidation by mitochondria, diminish endotoxin detoxification by liver homogenates, or greatly enhance susceptibility of the animals to endotoxin. Ethionine showed an effect intermediate between the other two agents. These findings are consistent with the hypothesis that the liver performs an important function in the detoxification of endotoxin by the oxidation of fatty acid residues in the endotoxin molecule.